2015
DOI: 10.1038/srep13911
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Piriformospora indica with Azotobacter chroococcum

Abstract: Microbial communities in rhizosphere interact with each other and form a basis of a cumulative impact on plant growth. Rhizospheric microorganisms like Piriformospora indica and Azotobacter chroococcum are well known for their beneficial interaction with plants. These features make P. indica /A. chroococcum co-inoculation of crops most promising with respect to sustainable agriculture and to understanding the transitions in the evolution of rhizospheric microbiome. Here, we investigated interactions of P. indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…This positive impact on P. indica growth was accompanied by an enhancing of the hyphal extension (Figure 2e) with delayed sporulation, but no effect on hyphal diameter was observed (Figure 2d). Similar results were reported recently by Bhuyan et al [20] for the co-culture of the P. indica with the Azotobacter strain WR5 on the same Kaefer agar medium, showing a highly significant growth stimulation in comparison with other Azotobacter strains. A. chroococcum is a well-known free-living, N-fixing rhizobacterium, which is capable of improving plant growth through nitrogen fixation or by the production of growth-promoting substances [21].…”
Section: Effect Of the Soil Bacteria On The Growth Of P Indicasupporting
confidence: 91%
See 1 more Smart Citation
“…This positive impact on P. indica growth was accompanied by an enhancing of the hyphal extension (Figure 2e) with delayed sporulation, but no effect on hyphal diameter was observed (Figure 2d). Similar results were reported recently by Bhuyan et al [20] for the co-culture of the P. indica with the Azotobacter strain WR5 on the same Kaefer agar medium, showing a highly significant growth stimulation in comparison with other Azotobacter strains. A. chroococcum is a well-known free-living, N-fixing rhizobacterium, which is capable of improving plant growth through nitrogen fixation or by the production of growth-promoting substances [21].…”
Section: Effect Of the Soil Bacteria On The Growth Of P Indicasupporting
confidence: 91%
“…In a study on differentially expressed proteins of P. indica co-cultured with A. chroococcum was reported the up-regulation of ENO1 (2-phosphoglycerate dehydratase) and Ure D fungi genes, suggesting that the bacterium could trigger the uptake of hexose sugar by the activation of several glucose transporters. ENO1 is one of the key regulatory enzymes of glycolysis [20]. Ure D is one of the accessory proteins of the apoprotein UreABC which is a nickel-dependent regulatory enzyme involved in recycling of urea [41].…”
Section: P Indica Amino Acid Content During DC With a Chroococcum Amentioning
confidence: 99%
“…This deficiency could be ameliorated by these bacterial helpers, as they possess several genes involved in secondary metabolite production, including PKS and NRPS. These secondary metabolites might supplement S. indica metabolism, bioenergetic capacity, activation of defense related genes and production of antibiosis compounds (Bonfante and Anca, 2009;Bhuyan et al, 2015;Salvioli et al, 2016), that ultimately raises the plant ISR. These strains possess also genes that might cooperate in restraining pathogen expansion, like strains P1-18 and P9-64 that might degrade oxalate produced by pathogens.…”
Section: Categorymentioning
confidence: 99%
“…Interestingly, it has been demonstrated that this fungus hosts an endobacterium, Rhizobium radiobacter (Sharma et al, 2008), which has endophytic as well as plant growthpromoting properties, although its functional role is not yet fully understood (Glaeser et al, 2016). Only few studies have demonstrated in vitro that particular bacterial strains can be detrimental for the growth of S. indica (Varma et al, 2013) or in contrast have stimulatory effects, like strain WR5 of Azotobacter chrococcum, which enhanced mycelial growth and sporulation of S. indica in vitro (Bhuyan et al, 2015). In the last few years, some researchers have developed co-inoculations (microbial consortia) of fungi and bacteria, searching synergisms between two beneficial microbes (Artursson et al, 2006;Collinge et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These interactions ecologically improved the fitness of soils to resist the stress through mechanisms such as producing some specific genes linked to cell-cell interaction, affecting changes in the metabolic mechanisms and thereby producing the resistance and resilience against the stress [51]. Interaction of Azotobacter and fungi leads to the increased growth of fungi through signaling secondary metabolites produced by Azotobacter, responsible for combating the stresses [52]. Although this kind of interaction is known to occur in the rhizosphere region, the exact nature of the molecular interaction is yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%